Importance of Melt Flow Direction during Injection Molding on Polymer Heat Sinks’ Cooling Efficiency - Guzej, Michal (Polymers (Basel), 2021)
Polymers with highly conductive fillers could possibly replace standardly used materials, such as aluminum and copper alloys, for passive cooling purposes. The main problem of the composite polymer-based heat sinks is that their high thermal conductivity is uneven. The orientation of this anisotropy is set according to the position of the highly thermally conductive filler. Its orientation is influenced by the melt flow during the polymer heat sink molding process. This article shows that change of the melt flow inside the mold cavity can improve the overall cooling efficiency of a polymer heat sink, which leads to lower temperatures on the heat source used. Two polymer heat sinks of identical geometries were produced. Their high thermal conductivity was given by the use of graphite flakes as the filler. The only difference between the heat sinks was in the position of the fan gate during their production. Different temperatures of the heat source between the two heat sinks were observed for the same measurement conditions. The measurements were conducted at Heatlab, BUT.